2016
DOI: 10.1530/jme-15-0159
|View full text |Cite
|
Sign up to set email alerts
|

3,5-T2 alters murine genes relevant for xenobiotic, steroid, and thyroid hormone metabolism

Abstract: The endogenous thyroid hormone (TH) metabolite 3,5-diiodo-l-thyronine (3,5-T 2 ) acts as a metabolically active substance affecting whole-body energy metabolism and hepatic lipid handling in a desirable manner. Considering possible adverse effects regarding thyromimetic action of 3,5-T 2 treatment in rodents, the current literature remains largely controversial. To obtain further insights into molecular mechanisms and to identify novel target genes of 3,5-T 2 in liver, we performed a microarray-based liver tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 91 publications
5
31
0
Order By: Relevance
“…Note, that the absence of thyrotoxic side effects of 3,5-T 2 treatment could not be replicated in other animal models (Jonas et al 2015, Lietzow et al 2016. In summary, apart from secretion from the thyroid gland tissue-specific action of T 3 is achieved by specific expression patterns of the deiodinase-encoding genes (Bianco 2011).…”
Section: Introduction Thyroid Hormone Physiology and Mode Of Actionmentioning
confidence: 92%
“…Note, that the absence of thyrotoxic side effects of 3,5-T 2 treatment could not be replicated in other animal models (Jonas et al 2015, Lietzow et al 2016. In summary, apart from secretion from the thyroid gland tissue-specific action of T 3 is achieved by specific expression patterns of the deiodinase-encoding genes (Bianco 2011).…”
Section: Introduction Thyroid Hormone Physiology and Mode Of Actionmentioning
confidence: 92%
“…3,5-T2, in contrast to its structural isomers 3,3 ′ -T2 and 3 ′ ,5 ′ -T2, is an active ligand for the classical T3 receptors (TR), where it binds with relative high affinity ( Table 4) and modulates transcriptional activity of TR, as indicated e.g., by rapid and powerful suppression of TSH in vivo, altered 3,5-T2 modulated gene expression in vitro and in several cellular models including anterior pituitary and liver (39,81,(85)(86)(87). In addition to its action on TSH suppression in thyrotropes, 3,5-T2 also stimulates growth hormone production and secretion in somatotrophs (86).…”
Section: 5-t2 Mechanism Of Action Involves Canonical Tr Signaling Amentioning
confidence: 99%
“…Controversial with respect to this set of observations, several other teams reported that administration of 3,5-T2 in rodent models (rat and mice, regular or high-fat diet, euthyroid or hypothyroid) dose-dependently resulted in significant suppression of the HPT axis as reflected by decreased TSH serum concentrations and/or pituitary beta-TSH transcript levels (6,39,87,94,95). Furthermore, thyromimetic effects typical for high circulating T3 were observed in the heart as analyzed by gene expression and/or morphological alterations suspicious of remodeling and fibrosis.…”
Section: 5-t2 Mechanism Of Action Involves Canonical Tr Signaling Amentioning
confidence: 99%
“…It can induce the mRNA synthesis of several genes such as TSH (Moreno et al, 1998), Dio1 (Baur et al, 1997) or TRβ (Ball et al, 1997). More generally, in mouse, 3,5-T2 has thyromimetic activity on the hypothalamus pituitary axis and lipid metabolism (Jonas et al, 2015) as well as on the liver transcriptome (Lietzow et al, 2016). In the killifish Fundulus heteroclitus, 3,5-T2 has been shown to be a ligand for TRβ (Mendoza et al, 2013), but this idea is still debated as 3,5-T2 has a very low binding potency on TR in rat and salmon (Darling et al, 1983).…”
Section: Even In Vertebrates the Classical Ligand Can Hide An Astonimentioning
confidence: 99%
“…Dio2 is therefore considered as an activating deiodinase. It also turns T3 into 3,5-T2, a TH derivative long considered as inactive but for which accumulative evidences suggest a biological role (Lietzow et al, 2016;Mendoza et al, 2013). The inner ring deiodination is catalyzed by the deiodinase type III (Dio3) which is considered as an inactivating deiodinase as it turns T4 into reverse T3 (3-3'-5'-T3 or rT3) and T3 into 3-3'-T2 ( Figure 1), compounds that have no biological activity (Chopra et al, 1978;Moreno et al, 2003).…”
Section: Introductionmentioning
confidence: 99%